Lithography: Hybrid Helical Magnetic Microrobots Obtained by 3D Template‐Assisted Electrodeposition (Small 7/2014). Issue 7 (April 2014) - Zeeshan, Muhammad A.; Grisch, Roman; Pellicer, Eva; Sivaraman, Kartik M.; Peyer, Kathrin E.; Sort, Jordi; Özkale, Berna; Sakar, Mahmut S.; Nelson, Bradley J.; Pané, Salvador
<x xml:space="preserve">Abstract</x> Hybrid artificial flagella (h‐ABF) consisting of a ferromagnetic alloy head and a helical polymer tail can be fabricated by sequential electrodeposition of a cobalt‐nickel alloy and polypyrrole inside a photoresist template patterned by 3D laser lithography. As M. A. Zeeshan, S. Pané, and co‐workers report on page 1284, the h‐ABFs are physically stable in an aqueous environment with a rigid connection between the metallic and the polymer segments. Controlled actuation of the microrobots by a rotating magnetic field is demonstrated in a fluidic environment with a focus on swarm control. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>